Current Insight on Eco-Friendly Concrete: A Review - Shaheda T. Akter; Allan Hawas (Buildings)
Concrete is known for its high structural performance and workability, but its environmental impact is significant in terms of the utilization of virgin resources and greenhouse gas emissions. To mitigate the negative climate effects of concrete, it is essential to continuously develop and adopt eco-friendly practices in the construction sector. This paper provides an overview of current practices, opportunities, and challenges for developing and adopting eco-friendly concrete. Promising paths for eco-friendly concrete construction include using supplementary cementitious materials (SCMs) instead of energy-intensive traditional cement, incorporating locally available, waste-based materials rather than virgin resources, adopting recycling and reusing techniques, employing advanced technologies, such as performance-enhanced concrete and carbon capture and utilization techniques, etc. Among the studied materials, some waste materials such as rice husk ash, mine tailings, and municipal solid waste ash have found potential and demand further research. The adoption of new materials in concrete and attributing them in practices faces significant social, economic, and regulatory challenges. Addressing these obstacles requires interdisciplinary research and development, the establishment of clear standards and incentives, and educating skilled professionals and efforts to raise social awareness.